Оптимизация динамической нагрузки в зубчатых зацеплениях планетарного механизма типа n x АЇ при контактной прочности - Матусевич, Владимир Анатольевич; Шарабан, Юрий Владимирович; Шехов, Александр Владимирович; Абрамов, Владимир Тимофеевич (НТУ "ХПИ", 2016)
Рассмотрена методика оптимизации динамической нагрузки в зубчатых зацеплениях многоступенчатого планетарного механизма типа n x АЇ с общим эпициклом. В качестве целевой функции оптимизации динамической нагрузки в зубчатых зацеплениях принята функция распределения коэффициента динамичности, параметрами которой являются передаточные отношения ступеней механизма. Приведены результаты сравнения двух оптимальных конструкций планетарного механизма, удовлетворяющих критериям минимума массы и динамической нагрузки соответственно. Предложены рекомендации по оптимальному проектированию вышеуказанных механизмов.

The method of optimization of the dynamic loading is considered in the toothed hooking of multi-stage planetary mechanism of type n x АЇ with a general epicycle. As an objective function of optimization of the dynamic loading the function of distributing of coefficient of dynamic quality the parameters of which are transmission relations of the stages of mechanism is accepted in the toothed hooking. Two formulas of determination of coefficient of dynamic quality of the external hooking of the planetary stage of mechanism are resulted. The type of formula is determined the type of the set data of the planetary stage. In one case it is the set number of points of mobile central wheel, and in other is a number of points of general epicycle. The results of comparison of two optimum constructions of planetary mechanism, satisfying the criteria of a minimum of mass and dynamic loading accordingly are presented. The results of joint minimization are resulted on two criteria simultaneously. The estimations of such minimization are indicated. Recommendations are offered to on.
Optimization of the dynamic loading in the toothed hooking of planetary mechanism of type n x АЇ at contact durability
Keywords: многоступенчатый планетарный механизм; коэффициент динамичности; минимизация массы; эпицикл; dynamic quality; minimization of mass